KAJIAN TERHADAP KUANTITAS DAN KUALITAS AIR DANAU LUT ATAS SEBAGAI SUMBER AIR BAKU BAGI MASYARAKAT KABUPATEN BENER MERIAH - Edy Armansyah; Ernawita, Ernawita; Abdul Malik (Media Bina Ilmiah, 2024)
Lake Lut Atas is administratively located in the KPH III protected forest area which is located on the slopes of Mount Burni Kul, Kampung Waq Pondok Sayur, Bukit District, Bener Meriah Regency, at an altitude of 2100 meters above sea level, with an area of ​​approximately 8 hectares. Lake Lut Atas has long been used as a source of raw water for people's lives. However, the use of Lake Lut Atas as a source of clean water has not been carried out optimally because there is still a lack of research that examines the quantity and quality of lake water to determine the feasibility of Lake Lut Atas as a source of raw water for the community. At present there is agricultural activity by the community on the outskirts of Lake Lut Atas. The condition of the lake at the time of the study was that a kind of water hyacinth was thriving which covered almost the entire body of the lake and siltation due to sedimentation which was feared could reduce the quantity and quality of water. The purpose of this study was to determine the physical and chemical parameter values ​​for the water quality of Lake Lut Atas and to determine the quality class (quality standard) of Tes Lake water according to Government Regulation No. 82 of 2001. The research results obtained physical parameters: lake depth 145.2 cm, temperature 23.2 °C, brightness 90 cm, and TDS 430.2 mg/L. For chemical parameters pH 8.05, DO 7.96 mg/L, COD 176.4 mg/L, BOD 12.294 mg/L, dissolved N-96.631 mg/L, and P 1.170 mg/L. As for the biological parameters, the total Coliform bacteria content was 48 Ind/ml.